Identifikasi Sleep Hygiene Lansia di Wilayah Kerja Puskesmas Rawasari Kota Jambi - hidayat, Muhammad; Hesty, Hesty (Prosiding Seminar Kesehatan Nasional, 2023)
The degenerative process in the elderly will cause a decline in function, one of which is physiological function. The decline in physiological function that is most often experienced by the elderly is a decrease in the need for rest and sleep. Sleep needs that are met in quality and quantity can improve the quality of life. One of the best ways to achieve sound sleep in the elderly is with sleep hygiene. Sleep can be influenced by an exercise or habit called sleep hygiene. Exercise or good sleep hygiene habits can prevent the development of sleep disorders. This research aims to determine the description of sleep hygiene for the elderly in the working area of the Rawasari Health Center, Jambi City. This research is a type of non-experimental research with a descriptive survey design, using quantitative methods and a cross-sectional approach. The results provide information that the majority or 110 elderly people (70.5%) out of 156 people are female. The sleep hygiene score for elderly people in the Rawasari Health Center working area, Jambi City, was 112 people (71.8%) categorized as good, 41 people (26.3%) categorized as moderate and 3 people (1.9%) categorized as bad. It can be concluded that the sleep hygiene score for elderly people in the Rawasari Health Center working area, Jambi City, is in the majority category as good.